Innovation as a strategic moderator in the link between corporate governance, interest coverage ratio, and financial distress - Susilowati, Nurdian; Nurhalizah, Nurhalizah (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study aims to determine the effect of corporate governance and interest ratio on financial distress with innovation as a moderating. The population of this study was LQ45-indexed companies on the Indonesia Stock Exchange for the 2019-2023 period. The sampling technique used was purposive sampling, which obtained 110 analysis units. This study uses descriptive statistical analysis and logistic regression analysis. The results of this study found that the board of commissioners and the board of directors did not have a significant effect on financial distress. Meanwhile, the audit committee and interest coverage ratio significantly and negatively affected financial distress. Innovation could not moderate the board of commissioners and the audit committee on financial distress. Innovation was able to weaken the influence of the board of directors on financial distress. Innovation strengthened the impact of the interest coverage ratio on financial distress.